2014
DOI: 10.15252/emmm.201303671
|View full text |Cite
|
Sign up to set email alerts
|

Selective clearance of aberrant tau proteins and rescue of neurotoxicity by transcription factor EB

Abstract: Accumulating evidence implicates impairment of the autophagy-lysosome pathway in Alzheimer's disease (AD). Recently discovered, transcription factor EB (TFEB) is a molecule shown to play central roles in cellular degradative processes. Here we investigate the role of TFEB in AD mouse models. In this study, we demonstrate that TFEB effectively reduces neurofibrillary tangle pathology and rescues behavioral and synaptic deficits and neurodegeneration in the rTg4510 mouse model of tauopathy with no detectable adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
299
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 316 publications
(320 citation statements)
references
References 61 publications
20
299
1
Order By: Relevance
“…We have recently shown that trehalose activates TFEB through inhibition of AKT, a negative regulator of TFEB [64]. A growing body of evidence shows that TFEB-mediated enhancement of clearance via lysosomal biogenesis and increased autophagic flux counteracts the accumulation of different proteinaceous materials and slows disease progression in various animal models of disease [2125,37,65]. Notably, in these studies, clearance of the abnormally accumulated material exerts protective effects against neuronal death, regardless of the nature of the stored material and the pathway by which it would normally be degraded.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that trehalose activates TFEB through inhibition of AKT, a negative regulator of TFEB [64]. A growing body of evidence shows that TFEB-mediated enhancement of clearance via lysosomal biogenesis and increased autophagic flux counteracts the accumulation of different proteinaceous materials and slows disease progression in various animal models of disease [2125,37,65]. Notably, in these studies, clearance of the abnormally accumulated material exerts protective effects against neuronal death, regardless of the nature of the stored material and the pathway by which it would normally be degraded.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inducing TFEB activity in cellular and animal models of Hungtington's disease can reduce protein aggregation and improves neurological functions (Sardiello et al, 2009;Tsunemi et al, 2012). Furthermore, TFEB overexpression or its pharmacological activation in cellular and mouse models of Alzheimer's disease and other tauopathies can also reduce the amount of protein aggregates (Chauhan et al, 2015;Polito et al, 2014;Xiao et al, 2014Xiao et al, , 2015, which results in a reduction of neurodegeneration and improvement of behavioral deficits. Therefore, promotion of intracellular clearance through the induction of TFEB activity might represent a common therapeutic strategy for neurodegenerative disorders.…”
Section: Tfeb As a Therapeutic Target For Diseasesmentioning
confidence: 99%
“…TFEB is able to reduce neurofibrillary tangle pathology, rescue behavioral and synaptic deficits, and effectively compensate for neurodegeneration in the rTg4510 mouse model of autopathy. 109 Based on these studies, Stern et al 107 proposed that autophagy and lysosomal dysfunction may be emerging mechanisms of NM toxicity (ie, NP-mediated lysosome-dependent autophagy). Autophagy can play dual roles in cell survival after interaction with NPs: autophagy can play a cytoprotective role or a cytotoxic role under different conditions.…”
mentioning
confidence: 99%